Preparation and characterization of zerovalent iron nanoparticles. Issue 2 (4th May 2018) - Huyen, Nguyen Thi Thanh; Nhung, Nguyen Hong; Thanh, Le; Khanh, Pham Duy; Lam, Tran Dai; Son, Hoang Anh
Abstract: Zerovalentiron nanoparticles (nZVI) were prepared by the reactive method of iron Fe2 O3 with the reducing agent of hydrogen generated from electrolysis of water. Investigation on the formation conditions of the Fe 0 nanocrystals showed that by carrying out the reaction with the reduction time of 90 minutes at 400°C, a hydrogen flow rate of 350 ml/min, Fe 0 nanoparticles were obtained with diameter concentrated on 36.19 nm. Characteristic properties of the material (morphology, structure, particle size distribution) were investigated by X‐Ray diffraction (XRD), scanning electron microscopy and dynamic light scattering methods.